ANALYSIS OF GOMBANG AT VILLAGE KUALA MERBAU DISTRICT PULAU MERBAU MERANTI MARITIME RIAU PROVINCE - Rizky Rachmattullah; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The Research on the analysis of gombang was conducted in October until November2014 in Village Kuala Merbau, District Pulau Merbau, Meranti Maritime, Riau Province. Theaims of this study were to great investmens, gross income, net income and feasibillity usinggombang. The method used to this case study, respondents were selected through purposivesampling of gombang of 7,5 and 3 bags.The results of this study indicate that investmens gombang 7 bags Rp 19.352.000, 5bags Rp 16.103.000 and 3 bags Rp 9.835.000. Gross income gombang 7 bags Rp110.088.000, 5 bags Rp 84.744.000 and 3 bags Rp 42.768.000. Net Income gombang 7 bagsRp 59.928.000, 5 bags Rp 44.253.000 and 3 bags Rp 19.800.000. Feasibility of gombang for7 bags RCR 2,19 and PPC 2,94. 5 bags RCR = 2,09 and PPC = 3,32. 3 bags RCR = 1,86 andPPC = 9,49. This shows that effort gombang gear profiable and feasibilty to proceed.Keywords : Gombang, investment, income, feasibility